Serum Amyloid A in Inflammatory Rheumatic Diseases: A Compendious Review of a Renowned Biomarker - Sorić Hosman, Iva; Kos, Ivanka; Lamot, Lovro (Frontiers in Immunology, 2021)
Serum amyloid A (SAA) is an acute phase protein with significant importance for the inflammatory rheumatic diseases (IRD). SAA contains cytokine and chemokine-like properties, activates transcription factors via several defined receptors and induces tissue degrading enzymes such as matrix metalloproteinases. The central role of SAA in pathogenesis of IRD has been confirmed by recent discoveries, including its involvement in the activation of the inflammasome cascade and recruitment of interleukin 17 producing T helper cells. Clinical utility of SAA in IRD was originally evaluated nearly half a century ago. From the first findings, it was clear that SAA could be used for evaluating disease severity and monitoring disease activity in patients with rheumatoid arthritis and secondary amyloidosis. However, cost-effective and easily applicable markers, such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), overwhelmed its use in clinical practice. In the light of emerging evidence, SAA has been discerned as a more sensitive biomarker in a wide spectrum of IRD, especially in state of subclinical inflammation. Furthermore, a growing number of studies are confirming the advantages of SAA to many other biomarkers in predicting and monitoring response to biological immunotherapy in IRD patients. Arising scientific discoveries regarding the role of SAA, as well as delineating SAA and its isoforms as the most sensitive biomarkers in various IRD by recently developing proteomic techniques are encouraging the revival of its clinical use. Finally, the most recent findings have shown that SAA is a biomarker of severe Coronavirus disease 2019 (COVID-19) and poor prognosis, which could have enormous clinical relevance in a new era of coexistence of IRD patients and SARS-CoV-2. The aim of this review is to provide a comprehension of the SAA-involving immune system network with emphasis on mechanisms relevant for IRD, as well as to discuss usefulness of SAA as a biomarker in various IRD. Therefore, over a hundred original papers were collected through an extensive PubMed and Scopus databases search. These recently arising insights will hopefully lead to a better management of IRD patients and might even inspire the development of new therapeutic strategies with SAA as a target.